IMPLEMENTASI KEBIJAKAN MITIGASI BENCANA PADA BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN SUMEDANG - Dadan Setia Nugraha; Alan Setiawan; Destrya Prematuri Agningsih; Dwi Nurul Aprilianti; Endas Sutisna; Lutfi Yuliani (Journal Of Regional Public Administration (JRPA), 2020)
The purpose of this study was to determine the effect of Disaster Emergency Management Operations on Work Effectiveness in the Head of Emergency and Logistics Section at the Regional Disaster Management Agency of Sumedang Regency. The research method used in this research is quantitative research method with two data collection methods, namely literature study and field study which includes observation, questionnaires, interviews and documentation. The distribution of questionnaires was carried out to all ASN (State Civil Apparatus) and Non-ASN (Pusdalops) employees in the Regional Disaster Management Agency of Sumedang Regency, totaling 40 people. Based on the results of the study, it is known that the Operational Planning for Disaster Emergency Management at the Section Head for Emergency and Logistics at the Regional Disaster Management Agency of Sumedang Regency is 88.4%. Furthermore, the work effectiveness of the Head of Emergency and Logistics Section in the Regional Disaster Management Agency of Sumedang Regency is 90.5%. Based on the correlation test, it is known that there is a very strong relationship between the Operational Planning for Disaster Emergency Management with the Work Effectiveness of the Head of Emergency and Logistics Section in the Regional Disaster Management Agency of Sumedang Regency with a correlation coefficient of 0.808. The Effect of Disaster Emergency Management Operations Planning on Work Effectiveness in the Section Head for Emergency and Logistics in the Regional Disaster Management Agency of Sumedang Regency based on the determination test is in the strong category with a determination coefficient of 0.653 or if a percentage is 65.3%. While the remaining 34.7% is influenced by other factors not examined in this study.